The Mappıng of Issues Regardıng the Adoptıon of E-Busıness Among SMEs in Fıve Contınents - Aryani, Sinta (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
E-business in this VUCA era has been increasingly gaining scholars attention especially in the SMES sector. This systematic literature study with the objective to identify the issues faced by SMEs on five continents when they want to adopt e-business. Data was taken from the collection of literature on journal portals such as Google Scholar, Academia, Scopus, and Elsevier, with keywords SMEs, e-business, information technology, digital transformation, and competitiveness. The collection of the literature is not limited by the country. The more countries that are taken, the more this paper reflects the real problems faced by SMEs when they want to adopt e-business. There are 115 collected pieces of literature representing the five continents that exist. The findings obtained from this paper are that all SMEs on five continents have similar issues when they want to adopt e-business. The findings are classified into Technology, Organization, and Environment (TOE) to facilitate classification and analysis and it is found that Technology in terms of business communication, Organization in terms of human resources, and Environment in terms of ICT infrastructure are the most common issues when SMEs want to adopt e-business. However, each continent has its own characteristics.